The value of bindings - Marc Bacchetta; Roberta Piermartini (World Trade Organization (WTO), 2011)
One of the goals of the multilateral trading system is to enhance the stability and predictability of the environment in which traders operate.Binding tariffs at the WTO reduces the scope for their discretionary use. But, countries have bound tariffs at ceiling levels often substantially above the level of applied tariffs. Therefore, whether the ceiling rate at which countries have committed at the WTO is sufficient to diminish trade policy volatility is an empirical question. Using a recently built database on applied tariffs covering over 100 countries for the period 1996 to 2009, we find evidence that countries do vary tariffs. Most importantly, we find evidence that applied tariffs of tariff lines that are bound are more likely to be decreased and less likely to be increased, and that this taming effect of the binding decreases with the level of the water (i.e. the gap between bound and applied tariff). This finding is robust to controlling for political economy determinants of tariffs and to factors related to the economic cycle.
Keywords: F1; 330; water in the tariff; weak commitments; tariff volatility; trade policy uncertainty; World Trade Organization; trade agreements